Firm performance in the craft industry: mediating role of entrepreneur’s competencies - Mohd Rosli Mohamad; Mohd Rafi Yaacob; Rosman Mahmood (2012)
The craft industry is the oldest industry in any society, including Malaysia. However, the Malaysian craft industry is rather small in size and scattered all over the country. Regionally, this industry has lost its competitive advantage to neighbouring countries, especially Thailand and Indonesia. China and Vietnam also exert a great challenge to Malaysian crafters. Probably due its primitive nature, studies on economic and entrepreneurial dimensions of the industry are not much seen in the last few decades. This paper attempts to show how entrepreneurial process enhances firm performance. It is argued that entrepreneur process through entrepreneur‟s experience, education and training will improve entrepreneur‟s competencies, which ultimately enhance firm performance. Using 100 samples collected from small crafters in Terengganu, this study shows that managerial competencies mediated the relationship between entrepreneur‟s experiences and firm performance. Knowledge in this paper would provide better explanation for firm performance in the craft industry. At the same time, entrepreneurs and policy makers would be able to improve their knowledge and hence contribute to superior performance of the firms and industry.